Association between metabolic activity of visceral adipose tissue and retinal vein occlusion: a preliminary 18F-FDG PET/CT study - Choi, Kwang-Eon; Joung, Chanmin; Yoon, Eungyu; Chung, Hyun Woo; Pahk, Ki Joo; Pahk, Kisoo (Frontiers in Endocrinology, 2025)
BackgroundRetinal vein occlusion (RVO) predominantly occurs in individuals over the age of 50, and obesity is a recognized risk factor for its development. The pro-inflammatory metabolic activity of visceral adipose tissue (VAT), which elevates systemic inflammation, is regarded as a key underlying mechanism contributing to the detrimental effects of obesity on atherosclerosis and hypercoagulability in RVO. In this study, we aimed to evaluate the inflammatory metabolic activity of VAT using 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) and to examine its association with RVO.Material and methodsA total of 22 elderly patients with RVO (aged ≥ 50 years) who underwent 18F-FDG PET/CT for routine health screening, along with 15 age-matched control participants who also underwent 18F-FDG PET/CT for routine health screening, were enrolled. The metabolic activity of VAT was assessed using its maximum standardized uptake value (SUVmax), while systemic inflammation was evaluated based on the SUVmax of the spleen and bone marrow (BM), as well as C-reactive protein (CRP) levels.ResultsThe VAT SUVmax was higher in patients with RVO compared to the non-RVO group. Additionally, levels of systemic inflammation surrogate markers were elevated in patients with RVO relative to those without RVO. Furthermore, VAT SUVmax showed a positive correlation with systemic inflammation surrogate markers and was independently associated with the presence of RVO.ConclusionsThe metabolic activity of VAT, as assessed by 18F-FDG PET/CT, was found to be associated with the presence of RVO and correlated with the degree of systemic inflammation. Therefore, VAT SUVmax may serve as a potential surrogate marker for obesity-related VAT inflammation linked to RVO.